Hubungan Merokok Terhadap Mual, Muntah, dan Nyeri Pasien Pasca Operasi di RS Permata Medika Semarag: Hubungan Merokok Terhadap Mual, Muntah Dan Nyeri Pasien Pasca Operasi Spinal Anestesi - Hindria Elfanti; Dyah Restuning Prihati; Dwi Nur Aini (Poltekkes Kemenkes Malang, 2026)
Spinal anesthesia is widely used in surgery, but it can still cause pain and postoperative nausea and vomiting (PONV). Smoking is known to affect pain responses and the nausea center through neurophysiological mechanisms. This study aims to analyze the relationship between smoking habits and the incidence of nausea, vomiting, and pain levels in postoperative patients with spinal anesthesia at Permata Medika Hospital, Semarang. The study used a correlational design with a cross-sectional approach in 70 male respondents. Smoking habits were measured using the GATS, nausea and vomiting using the RINVR, and pain using the NRS. Analysis using the Spearman's rho test showed a significant relationship between smoking habits and nausea and vomiting (p < 0.05) with a negative direction, and a significant relationship between smoking habits and pain levels (p = 0.001; r = 0.390) with a positive direction. It was concluded that smoking habits are associated with nausea, vomiting, and pain levels after spinal anesthesia surgery.